Cognitive load in high school students during online learning amidst the Covid-19 pandemic: A qualitative study in Bantul, Indonesia - Novi Trilisiana; Haryanto Haryanto; Pujiriyanto Pujiriyanto; Wahyu Kurniawati; Jamiu Temitope Sulaimon (Universitas Negeri Yogyakarta, 2023)
The public doubts that learning can be meaningful and in-depth if done online. Moreover, the implementation of online learning still has weaknesses from upstream to downstream. This research focuses on the cognitive load in students when online learning begins to be carried out massively in Indonesia due to the Covid-19 pandemic. This qualitative study aims to identify high school students' experiences in Bantul while learning online during the pandemic. Data were collected for four months through observation, in-depth interviews, and documentation. The collected data were transcribed, coded, and analyzed for themes using cognitive load theory and learning technology. The results illustrate that high school students in Bantul experience extra effort in learning through online platforms due to the novelty of the online learning experience, distractions, subject matter presentation, and the impact of cognitive load on students' learning. This research enriches innovative strategies for managing online learning by learning technology science. It has contributions to the need to train teachers and students to carry out learning in an independent mode. Online learning, when managed by accommodating good theory and practice of learning technology, proves to be a strategic learning mode, especially amidst the challenges of the Covid-19 pandemic.